Do markup dynamics reflect fundamentals or changes in conduct? - Mikael Juselius; Moshe Kim; Staffan Ringbom (Bank of Finland, 2009)
Persistent shifts in equilibria are likely to arise in oligopolistic markets and may be detrimental to the measurement of conduct, related markups and intensity of competition. We develop a cointegrated VAR (vector autoregression) based approach to detect long-run changes in conduct when data are difference stationary. Importantly, we separate the components in markups which are exclusively related to long-run changes in conduct from those explained solely by fundamentals. Our approach does not require estimation of markups and conduct directly, thereby avoiding complex problems in existing methodologies related to multiple and changing equilibria. Results from applying the model to US and five major European banking sectors indicate substantially different behavior of conventional raw markups and conduct-induced markups.
URN:NBN:fi:bof-20140807229
Keywords: C32; C51; G20; L13; L16; 330; markups; cointegration; VAR; macroeconomic fundamentals; competition; banking